1998
DOI: 10.1126/science.281.5383.1668
|View full text |Cite
|
Sign up to set email alerts
|

MP1: A MEK Binding Partner That Enhances Enzymatic Activation of the MAP Kinase Cascade

Abstract: Signal transduction is controlled both by regulation of enzyme activation and by organization of enzymatic complexes with nonenzymatic adapters, scaffolds, and anchor proteins. The extracellular signal-regulated kinase (ERK) cascade is one of several evolutionarily conserved mitogen-activated protein (MAP) kinase cascades important in the regulation of growth, apoptosis, and differentiation. A two-hybrid screen was conducted to identify nonenzymatic components of this signaling cascade that might be important … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
345
1

Year Published

1999
1999
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 431 publications
(361 citation statements)
references
References 10 publications
15
345
1
Order By: Relevance
“…A specific phosphatase -such as PP2A (Anderson et al, 1990) -may be induced by IFN-α, thus resulting in the inactivation of MEK or ERK. Another possibility is that IFN-α may regulate the expression of docking proteins (Pawson and Scott, 1997;Schaeffer et al, 1998;Whitmarsh and Davis, 1998), eventually affecting the interaction between MEK and ERK, or between MEK and upstream kinases. Understanding the exact mechanism is important for our comprehension of the proper function of IFN-α and possibly to develop novel targets to strengthen the IFN-mediated anti-cancer effect.…”
Section: Discussionmentioning
confidence: 99%
“…A specific phosphatase -such as PP2A (Anderson et al, 1990) -may be induced by IFN-α, thus resulting in the inactivation of MEK or ERK. Another possibility is that IFN-α may regulate the expression of docking proteins (Pawson and Scott, 1997;Schaeffer et al, 1998;Whitmarsh and Davis, 1998), eventually affecting the interaction between MEK and ERK, or between MEK and upstream kinases. Understanding the exact mechanism is important for our comprehension of the proper function of IFN-α and possibly to develop novel targets to strengthen the IFN-mediated anti-cancer effect.…”
Section: Discussionmentioning
confidence: 99%
“…Examples of this have been identi®ed in S. cerevisiae, and recently in mammals (Schae er et al, 1998;Whitmarsh et al, 1998). JNK interacting protein (JIP1) selectively binds to MKK7 (MAPKK), MLK3 (MAPKKK) and HPK (MAPKKKK), thereby enhances the e ciency and speci®city of enzyme-substrate interactions (Whitmarsh et al, 1998).…”
Section: Stress Activated Kinases H Ichijomentioning
confidence: 94%
“…Our recent observations have suggested a potential role for the MP1-p14 complex in coupling MAP kinase signaling to Rho [126]. MP1 is a small protein (14 kDa) identified as a MEK1 and ERK1 binding partner [127]; p14 is a protein tightly associated with late endodomes and lysosomes that was subsequently found to interact with high affinity with MP1 [128][129][130]. Specifically, we have found that MP1-p14 is important for PAK phosphorylation of MEK1 and ERK activation during adhesion to fibronectin, and that siRNA-mediated depletion of the complex causes a spreading defect in fibroblasts in concert with the formation of dense circumferential F-actin and large vinculin containing adhesions [126].…”
Section: Erk Regulation Of Rho-rock Functionmentioning
confidence: 99%
“…One intriguing possibility is that MP1/p14 may incorporate into the dynein motor complex through the LC7-like motif in p14 and thus tether MEK1, ERK1 and PAK1 to the dynein motor complex on microtubules. Since MP1 binds preferentially to inactive MEK1 [127] and active PAK1 [126], one might speculate that MP1/ p14 could serve to integrate MEK and PAK signals into the microtubule and motor machinery. Alternatively, PAK1 bound to DLC1 through PAK1 N-terminus, might bridge the MP1/p14 dimer bound to its C-terminus to molecular motors on microtubules facilitating specific targeting to cellular sites of action (Fig.…”
Section: Erk and Microtubule And Motor Dynamicsmentioning
confidence: 99%
See 1 more Smart Citation